HUBUNGAN TINGKAT STRES, ASUPAN KALSIUM, DAN VITAMIN B6 TERHADAP KEJADIAN PREMENSTRUAL SYNDROME PADA MAHASISWI PROGRAM STUDI GIZI PROGRAM SARJANA UPN VETERAN JAKARTA - Nur Afifah Ameylia (2022)
Premenstrual syndrome are several symptoms before the starting menstruation which is indicated by physical, emotional, and behavioral changes (7-14 days premenstrual) that interfere with daily activities. The exact cause of PMS is unknown, but there are several factors that influence PMS, one of which is psychological factors and nutritional intake. This study aims to analyze the relationship between stress levels, calcium intake, and vitamin B6 with the incidence of PMS in UPNVJ female nutrition students. Using cross sectional study design and sampling technique with stratified random sampling are 66 respondents. Data was collected by filling out questionnaires and SQ-FFQ interviews. Bivariate analysis using chi-square test. The results of this research are showed that the prevalence of PMS symptoms in female students was in the category of no symptoms to mild symptoms (53.0%) and moderate to severe symptoms (47.0%), then showed that there was a relationship between stress levels (p = 0.000) and calcium intake (p = 0.012) with the incidence of premenstrual syndrome in female students, and vitamin B6 intake did not show a relationship (p = 0.782). To decrease complaints from PMS, students are expected to control something that triggers stress and needs micronutrient intake.